Predictive value of serum initial brain natriuretic peptide and troponin on functional prognosis in noncardiogenic patients with anterior and posterior circulation cerebral infarction - Wan-Ting Lu; Wen-Ting Du; De-Sheng Lu; Jie You; Hong-yan Li (Arquivos de Neuro-Psiquiatria)
Background Brain natriuretic peptide (BNP) and troponin have a close relationship with cardiogenic cerebral embolism (CCE), but their relationship with noncardiogenic patients with anterior circulation ischemia (ACI) and posterior circulation ischemia (PCI) is not clear. Objective To explore the predictive value of serum initial BNP and troponin on the functional prognosis of patients with noncardiogenic ACI and PCI. Methods Consecutive patients with first-episode cerebral infarction within 12 hours of symptom onset were enrolled in the present 1-year prospective cohort study. Serum levels of BNP and troponin were collected within 12 hours of onset. Infarction location was classified as ACI and PCI by magnetic resonance imaging (MRI). According to the modified Rankin Scale (mRS) score at 90 days after onset, ACI and PCI cases were respectively divided into a good prognosis group (mRS score between 0 and 2) and a poor prognosis group (mRS score between 3 and 6). The general state of health and results of laboratory examinations and other auxiliary examinations of all patients were recorded. Single-factor analysis and multivariate logistic regression analysis were used to assess the relationship between serum levels of BNP, troponin, and functional outcome. Results The multivariate logistic regression found that higher levels of initial BNP (odds ratio [OR] = 1.024; 95% confidence interval [CI]: 1.006–1.041; p = 0.007) and C-reactive protein (CRP) (OR = 1.184; 95%CI: 1.024–1.369; p = 0.022) were independent predictors of poor functional prognosis of noncardiogenic PCI at 90 days after onset after adjusting for age, gender, ethnicity, history of hypertension and of diabetes. Conclusions The levels of initial BNP and CRP were related to poor functional outcomes in noncardiogenic PCI patients at 3 months, independent of troponin.